The Legal Politics of Marital Rape under Law No. 12 of 2022: A Maqāṣid al-Sharī‘ah Perspective - Prayudi Rahmatullah; Saifullah Saifullah; Abbas Arfan; Abd. Rouf; Musataklima Musataklima (Universitas Darussalam Gontor, 2026)
This study examines the legal politics of marital rape regulation in Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) through the lenses of Responsive Legal Theory and Maqāṣid al-Sharī‘ah. It explores the paradigm shift in Indonesian law that redefines marital rape from a private matter into a public legal concern aimed at protecting victims of sexual violence within marriage. Using a normative juridical method with legislative and conceptual approaches, the study analyzes the legal-political background, state orientation, and legislative process behind the formulation and ratification of the law. The findings indicate that the inclusion of marital rape in the TPKS Law reflects a responsive legal character, emphasizing justice, victim protection, human rights recognition, and gender equality. However, significant challenges remain in its implementation, particularly regarding evidentiary issues and persistent cultural resistance. From the perspective of Maqāṣid al-Sharī‘ah, the criminalization of marital rape aligns with the protection of dignity (ḥifẓ al-‘irḍ), life (ḥifẓ al-nafs), and lineage (ḥifẓ al-nasl). The study concludes that integrating Responsive Legal Theory with Maqāṣid al-Sharī‘ah provides a strong conceptual foundation for strengthening the legitimacy and effectiveness of marital rape regulation in Indonesia and advancing substantive justice within the national legal system.